Double-Gene Copromoting Expression Analysis in tPA/GH Transgenic Goat Mammary Epithelial Cells and Thrombolytic Activity of tPA In Vitro. (6th May 2022) - Song, Shaozheng; Luo, Yaoling; Liu, Zhaoxia; Li, Dan; Ye, Junsong; He, ZhengYi
Abstract : Human tissue-plasminogen activator (tPA) is a thrombolytic drug widely used in the treatment of stroke, pulmonary thrombosis, acute myocardial infarction, and other thrombotic diseases. The double genes cointegrated into the organisms and cells can produce a synergistic effect, which will improve the expression level of the target gene. However, the study of the integration of the GH and tPA genes to improve the expression level of tPA has not yet been reported. In order to elucidate this, we generated monoclonal goat mammary epithelial cell lines with tPA/GH double-gene integration and analyzed the tPA expression level in single- and double-gene integrated cells. We selected the mammary gland-specific expressing vectors BLC14/tPA and BLC14/GH with the β -lactoglobulin gene as a regulatory sequence in our previous research. The tPA and GH genes were electronically cotransfected into goat mammary epithelial cells. Resistant cell lines were screened by G418, and transgenic monoclonal cell lines were confirmed by PCR. The tPA expression was induced by prolactin and detected in the cell induction solution after 48 h by ELISA and Western blotting. We detected the tPA biological activity in vitro by fibrin agarose plate assay (FAPA). The results showed that a total of 207 resistant monoclonal cells were obtained, including 126 cell lines with tPA monogenic integration and 51 cell lines with tPA/GH double-gene integration. The rate of double-gene integration was 24.6% (51/207). A total of 48 cells expressed tPA, of which 25.3% (19/75) cells expressed single gene, and 56.9% (29/51) cells expressed double genes. The concentration of tPA in single-gene-expressing cells was 8.0-64.0 μ g/mL, and the tPA level in double-gene-expressing cells was significantly higher (200-7200 μ g/mL). In addition, the tPA had a relatively strong in vitro thrombolytic activity determined by FAPA. The results showed that goat mammary epithelial cell lines with tPA/GH gene integration were successfully established by electrotransfection, and the expression level of tPA in double-gene integrated cell lines was significantly increased. This study provided a new way for the preparation of a transgenic goat and other animal with high tPA expression by somatic cell nuclear transfer. The findings also laid a foundation for efficient production of pharmaceutical proteins in transgenic animal mammary gland bioreactors in the future.